Respostas
respondido por:
2
3(x-2) =4(-x+3)
3x-6=-4x+12
3x+4x=12+6
7x=18
x=18/7
acho que é assim!
Espero ter ajudado!
bons estudos!
3x-6=-4x+12
3x+4x=12+6
7x=18
x=18/7
acho que é assim!
Espero ter ajudado!
bons estudos!
Anônimo:
Obrigado, realmente meu cálculo parece estar certo!
respondido por:
2
Correto!
3 (x - 2) = 4 · (-x+3)
3x - 6 = -4x +12
3x + 4x = 12 + 6
7x = 18
x = 18/7
3 (x - 2) = 4 · (-x+3)
3x - 6 = -4x +12
3x + 4x = 12 + 6
7x = 18
x = 18/7
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás